(untitled) (Research, Society and Development, 2019)
In this article, we reflect on the problem of the existence of a normative grammar and how it affects the speakers of linguistic communities, generating linguistic prejudice. We intend to show how writing still has a privileged space, which ends up opening margins for the transformation of natural linguistic rules into a straitjacket. We also intend to think of the language as a sign system put in process by the speakers - natural holders of a language faculty - being alive, therefore, having its system modified, within the predicted regularities, as it is a structure. From the process, which are the utterances, the discourses, we can reflect on language and discourse, perhaps solving the problem, based mainly on authors such as Bagno (1999, 2007), Greimas (1973, 1975), Hjelmslev ( 1975), Perini (1999, 2001) and Saussure (2006).